Twenty‐Four‐Hour Post‐Thrombolysis NIHSS Score As the Strongest Prognostic Predictor After Acute Ischemic Stroke: ENCHANTED Study - Shoujiang You; Yanan Wang; Xia Wang; Toshiki Maeda; Menglu Ouyang; Qiao Han; Qiang Li; Lili Song; Yang Zhao; Chen Chen; Candice Delcourt; Xinwen Ren; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2024)
Background This study was conducted to determine optimal predictive ability of National Institutes of Health Stroke Scale (NIHSS) measurements at baseline, 24 hours, and change from baseline to 24 hours after thrombolysis on functional recovery in patients with acute ischemic stroke who participated in the ENCHANTED (Enhanced Control of Hypertension and Thrombolysis Stroke Study). Methods and Results ENCHANTED was an international, multicenter, 2×2 quasifactorial, prospective, randomized open trial of low‐dose versus standard‐dose intravenous alteplase and intensive versus guideline‐recommended blood pressure lowering in thrombolysis‐eligible patients with acute ischemic stroke. Absolute (baseline minus 24 hours) and percentage (absolute change/baseline × 100) changes in NIHSS scores were calculated. Receiver operating characteristic curve analyses assessed performance of different NIHSS measurements on 90‐day favorable functional recovery (modified Rankin Scale [mRS] score 0–2) and excellent functional recovery (mRS score 0–1). Youden index was used to identify optimal predictor cutoff points. A total of 4410 patients in the ENCHANTED trial were enrolled. The 24‐hour NIHSS score had the highest discriminative ability for predicting favorable 90‐day functional recovery (mRS score 0–2; area under the curve 0.866 versus 0.755, 0.689, 0.764; P<0.001) than baseline, absolute, and percentage change of NIHSS score, respectively. The optimal cutoff point of 24‐hour NIHSS score for predicting favorable functional recovery was ≤4 (sensitivity 66.5%, specificity 87.1%, adjusted odds ratio, 9.44 [95% CI, 7.77–11.48]). The 24‐hour NIHSS score (≤3) was the best predictor of 90‐day excellent functional recovery (mRS score 0–1). Findings were consistent across subgroups, including sex, race, baseline NIHSS score, stroke subtype, and age. Conclusions In thrombolysis‐eligible patients with acute ischemic stroke, 24‐hour NIHSS score (optimal cutpoint of 4) is the strongest predictor of 90‐day functional recovery over baseline and early change of NIHSS score. Registration URL: https://clinicaltrials.gov. Unique Identifier: NCT01422616.